2010
DOI: 10.1051/kmae/2010024
|View full text |Cite
|
Sign up to set email alerts
|

C and P in aquatic food chain: A review on C:P stoichiometry and PUFA regulation

Abstract: Key-words:aquatic ecosystem, grazing food chain, microbial loop, PUFA, stoichiometry, homeostasis Carbon (C) and phosphorous (P) regulation in aquatic food chains are transferred from lower to upper trophic levels primarily as polyunsaturated fatty acids (PUFAs) and C:P stoichiometry. The majority of C is transferred through algal based pathway. Microbial loop, though optionally contributes to C transfer, highly constrained by P limitation and bacterial predator type. Lack of essential PUFAs in bacteria is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 89 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Azim et al (2002 a, b, c) found 15-29% ash, 23-32 % protein, 2-5 % lipids and 33% carbohydrate in periphyton from bamboo substrates in their experimental earthen ponds. Moreover, the sestonic algal community is rich in ω-3 PUFAs (Saikia and Nandi, 2010), and because attached life forms on aquatic substrates (as periphyton) have similar genetic origins, they also can be a source of ω-3 PUFAs for higher trophic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Azim et al (2002 a, b, c) found 15-29% ash, 23-32 % protein, 2-5 % lipids and 33% carbohydrate in periphyton from bamboo substrates in their experimental earthen ponds. Moreover, the sestonic algal community is rich in ω-3 PUFAs (Saikia and Nandi, 2010), and because attached life forms on aquatic substrates (as periphyton) have similar genetic origins, they also can be a source of ω-3 PUFAs for higher trophic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid data were categorized by diet tracers (Table ; Belicka et al., ) and further organized into polyunsaturated fatty acids (PUFAs), saturated fatty acids (SAFAs), and monounsaturated fatty acids (MUFAs). Fatty acids were also organized by common essential fatty acids that are known to affect fish growth and development: eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and arachidonic (ARA) (see Saikia & Nandi, for a review). In addition to fatty acid and nutrient analyses, algal, bacterial, and fungal biovolume were used to calculate a ratio of autotrophic to heterotrophic organisms (A:H biovolume ratio).…”
Section: Methodsmentioning
confidence: 99%
“…The Florida Everglades is an ideal system to test these adaptive hypotheses because periphyton mats are the primary basal resource in this area (Browder, Gleason, & Swift, ; Trexler, Gaiser, Kominoski, & Sanchez, ) and are composed of complex assemblages of autotrophs (green algae, diatoms, and cyanobacteria) and heterotrophs (fungi and bacteria; Gaiser et al., ). Both autotroph and heterotroph components of Everglades periphyton communities respond rapidly to changes in water chemistry (Gottlieb, Gaiser, & Lee, ; Noe, Childers, & Jones, ; Pan, Stevenson, Vaithiyanathan, Slate, & Richardson, ), such as when phosphorus is added, because the Everglades ecosystem is naturally oligotrophic (Gaiser et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, if dissolved inorganic N or P becomes depleted, C incorporation through photosynthesis is not balanced by the incorporation of the other nutrients, resulting in an increase in the C:N and C:P ratios of the cells (Berman-Frank and Dubinsky 1999;Geider and La Roche 2002;Sterner and Elser 2002). The elemental composition of the algal prey influences the excretion rates of predators (Malzahn et al 2010), and the metabolic cost for maintaining stoichiometric homeostasis can affect predator growth rate (Boersma et al 2008, Saikia andNandi 2010). While this is well documented in metazoan grazers, less is known about protozoan grazers.…”
Section: Introductionmentioning
confidence: 99%